(untitled) - Doran, Susan (New York, 2005)
This new study of Tudor international relations is the first in nearly thirty years.Glenn Richardson and Susan Doran have assembled a team of scholars who bring fresh developments in cultural, gender and institutional history to bear upon the question of England's place in Europe and beyond between 1485 and 1603.
Keywords: Tudor, House of,Great Britain,Great Britain,England; History,Foreign relations,Civilization; Tudors, 1485-1603,1485-1603,16th century